Peningkatkan Kemampuan Guru SD Dalam Menggunakan Alat Peraga Matematika Melalui Kegiatan Workshop - Suandi Suandi (Lembaga Penelitian dan Pendidikan Mandala, 2018)
This study is based on the limitations of teachers' skills in using props. Various technical has been done to improve the skill mentioned above but no one has achieved result as expected. The School Action Research was carried out in cluster 01 of Pringgarata District. Researchers want to get answers, Will workshop activities can improve the ability of teachers in using props. The target is the teachers of class IV, V, and VI number of 18 people, spread over 6 SDN targeted. This research uses descriptive analysis method. The result of the research shows the improvement of teacher skill of class IV, V, VI before, and after Workshop. This shows that Workshop is the right activity in improving teacher ability in using props